Inspired by the East how the Islamic world influenced Western art - Greenwood, William (Curator); De Guise, Lucien (The British Museum Press, 2019)
Inspired by the East is a contemporary and original examination of the artistic encounters between East and West, revealing how European and North American visual arts were inspired by the Islamic world.